2011
DOI: 10.1161/circulationaha.111.034850
|View full text |Cite
|
Sign up to set email alerts
|

Immune Activation Resulting From NKG2D/Ligand Interaction Promotes Atherosclerosis

Abstract: Background The interplay between the immune system and abnormal metabolic conditions sustains and propagates a vicious feedback cycle of chronic inflammation and metabolic dysfunction that is critical for atherosclerotic progression. It is well established that abnormal metabolic conditions, such as dyslipidemia and hyperglycemia, cause various cellular stress responses that induce tissue inflammation and immune cell activation, which in turn exacerbate the metabolic dysfunction. However, molecular events link… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
63
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(69 citation statements)
references
References 41 publications
5
63
0
1
Order By: Relevance
“…In addition, hyperlipidemia, diabetes, infection, and injury can stimulate expression of various ligands of the KLRK1 receptor on endothelial cells and macrophages, among other cells. Activation of the KLRK1 receptor causes vigorous production of cytokines by NK, NKT, and other cells while KO of KLRK1 markedly reduced atherosclerosis as noted previously (1118,1989).…”
Section: G Redundancy In Leukocyte Signalingsupporting
confidence: 66%
See 1 more Smart Citation
“…In addition, hyperlipidemia, diabetes, infection, and injury can stimulate expression of various ligands of the KLRK1 receptor on endothelial cells and macrophages, among other cells. Activation of the KLRK1 receptor causes vigorous production of cytokines by NK, NKT, and other cells while KO of KLRK1 markedly reduced atherosclerosis as noted previously (1118,1989).…”
Section: G Redundancy In Leukocyte Signalingsupporting
confidence: 66%
“…Expression of KLRK1 ligands were markedly increased in hyperlipidemic as well as diabetic mice. KLRK1 KO markedly decreased atherosclerosis by 80% (1989). The KLRK1 receptor and ligand system seems to work similarly to TLR ligation to induce rapid and generous production of inflammatory cytokines including IFN-␥, TNF-␣, CXCL1, IL-1␤, IL-6, and IL-12 (1118).…”
Section: Natural Killer T-cells and Relatedmentioning
confidence: 99%
“…Previous work showed that MICA/B is expressed in endothelial cells and foam cells in atherosclerotic lesions of type 2 diabetic patients (Xia et al, 2011). To examine whether MICA/B is expressed in atherosclerotic lesions in general, we performed immunohistochemical staining of MICA/B in 10 autopsy-derived aortic samples.…”
Section: Mica/b Expression In Foam Cells Infiltrating Atheroscleroticmentioning
confidence: 99%
“…Recently, inhibition of NKG2D functions was shown to suppress inflammation by immune cells and reduce aortic plaque formation in mice (Xia et al, 2011). The same work also showed that endothelial cells and macrophages infiltrating atherosclerotic plaques express MICA/B in patients with type 2 diabetes (Lin et al, 2012;Xia et al, 2011). were used as MDMs.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, the authors detected a very high concentration of shed MULT1 in the sera of Apoe -/-mice exhibiting severe atherosclerosis and liver inflammation. Given that these autoimmune injuries observed in this mouse model depend on NKG2D activity [5], it was unlikely that shed MULT1 exert an inhibitory effect on immunity.…”
mentioning
confidence: 98%